2012
DOI: 10.1029/2012rs005023
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric signatures of Tohoku‐Oki tsunami of March 11, 2011: Model comparisons near the epicenter

Abstract: [1] We observe ionospheric perturbations caused by the Tohoku earthquake and tsunami of March 11, 2011. Perturbations near the epicenter were found in measurements of ionospheric total electron content (TEC) from 1198 GPS receivers in the Japanese GEONET network. For the first time for this event, we compare these observations with the estimated magnitude and speed of a tsunami-driven atmospheric gravity wave, using an atmosphere-ionosphere-coupling model and a tsunami model of sea-surface height, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
208
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(228 citation statements)
references
References 36 publications
(71 reference statements)
17
208
0
3
Order By: Relevance
“…In addition, when IGWs reach and interact with the ionospheric plasma, it will result in a perturbation in the plasma density and velocity due to collisions between the ions and neutral molecules. Recently, several works have been performed and validated in detecting the tsunami by GNSS ionospheric TEC, e.g., tsunamis following the great 2004 Mw = 9.1 Sumatra earthquake, 2010 Chile earthquake and 2011 Mw = 9.0 Tohoku Earthquake (Rolland et al, 2010;Occhipinti et al, 2013;Galvan et al, 2012). Furthermore, numerical modeling of IGW reproduces the main features observed in the airglow images, which show interesting likenesses between the model and data, and explain the nature of the airglow observation and the role of the bathymetry in the ionospheric observation .…”
Section: Tsunami-generated Gravity Wave Couplingmentioning
confidence: 99%
“…In addition, when IGWs reach and interact with the ionospheric plasma, it will result in a perturbation in the plasma density and velocity due to collisions between the ions and neutral molecules. Recently, several works have been performed and validated in detecting the tsunami by GNSS ionospheric TEC, e.g., tsunamis following the great 2004 Mw = 9.1 Sumatra earthquake, 2010 Chile earthquake and 2011 Mw = 9.0 Tohoku Earthquake (Rolland et al, 2010;Occhipinti et al, 2013;Galvan et al, 2012). Furthermore, numerical modeling of IGW reproduces the main features observed in the airglow images, which show interesting likenesses between the model and data, and explain the nature of the airglow observation and the role of the bathymetry in the ionospheric observation .…”
Section: Tsunami-generated Gravity Wave Couplingmentioning
confidence: 99%
“…The TEC disturbance generated above the epicentre radially propagates with the velocity of acoustic waves in the ionosphere, e.g. approximately 1 km/s910. The intensity of southward (northward) propagation of the TEC disturbance was clearly visible in the northern (southern) hemisphere, while that of northward (southward) propagation was not clearly observed, because the asymmetrical intensity of northward and southward propagation is caused by the different plasma motion forced to the direction of magnetic field lines11.…”
mentioning
confidence: 99%
“…After developing a method to measure the ionospheric total electron content (TEC) between a GPS satellite and its receivers on the ground, using the phase difference between two carrier signals from the satellite, the ionospheric disturbance can be detected as a TEC disturbance. In particular, after increase in the number of ground-based GPS receivers, spatio-temporal images of the TEC disturbance generated by the EQ and tsunami allow identification of the epicentre5 and tsunami propagation6789. The TEC disturbance generated above the epicentre radially propagates with the velocity of acoustic waves in the ionosphere, e.g.…”
mentioning
confidence: 99%
“…identified Rayleigh wave-induced disturbances propagating with a speed of 2.3-3.3 km s À1 using GPS receivers in Taiwan. Rolland et al (2011a,b) and Galvan et al (2012) analyzed the GPS data in Japan and identified three propagation speeds in the observed ionospheric disturbances and attributed them to gravity waves induced by tsunami (200-300 m s À1 ) and direct acoustic waves (1000 m s À1 ) and those excited by the Rayleigh waves (3400 m s À1 ). Far-field data of the tsunami-induced ionospheric disturbances were, for the first time, observed by an airglow camera located in Hawaii Occhipinti et al (2011) modeled these signals by internal gravity waves.…”
Section: The Case Of the Great Sumatra-andaman Earthquakementioning
confidence: 98%